Single and Multi‐Mode Directional Lasing from Arrays of Dielectric Nanoresonators. Issue 3 (27th January 2021) - Azzam, Shaimaa I.; Chaudhuri, Krishnakali; Lagutchev, Alexei; Jacob, Zubin; Kim, Young L.; Shalaev, Vladimir M.; Boltasseva, Alexandra; Kildishev, Alexander V.
Abstract: The strong electric and magnetic resonances in dielectric subwavelength structures have enabled unique opportunities for efficient manipulation of light–matter interactions. Besides, the dramatic enhancement of nonlinear light–matter interactions near so‐called bound states in the continuum (BICs) has recently attracted enormous attention due to potential advancements. However, the experimental realizations and the applications of high‐Q factor resonances in dielectric resonances in the visible have thus far been considerably limited. In this work, the interplay of electric and magnetic dipoles in arrays of dielectric nanoresonators is explored. The experimental realization of high‐Q factor resonances in the visible through the collective diffractive coupling of electric and magnetic dipoles is reported. It is also shown that coupling the Rayleigh anomaly of the array with the dipoles of the individual nanoresonators can result in the formation of different types of BICs. The resonances in the visible regime is utilized to achieve lasing action at room temperature with high spatial directionality and low threshold. Finally, multi‐mode, directional lasing is experimentally demonstrated and the BIC‐assisted lasing mode engineering in arrays of dielectric nanoresonators is studied. It is believed that the results enable a new range of applications in flat photonics through realizing on‐chip controllable single and multi‐wavelength micro‐lasers. Abstract : This paper reports on the experimental realization of an on‐chip laser with an array of dielectric nanoresonators. The collective coupling of the electric and magnetic dipole modes of individual resonators with the Rayleigh anomaly of the entire array provides feedback for the laser. Changing the lasing array design allows for tuning its operation from a single‐ to multi‐wavelength regime.